Cytogenetic Diversity of Simple Sequences Repeats in Morphotypes of Brassica rapa ssp. chinensis - Zheng, Jin-shuang; Sun, Cheng-zhen; Zhang, Shu-ning; Hou, Xi-lin; Bonnema, Guusje (Frontiers in Plant Science, 2016)
A significant fraction of the nuclear DNA of all eukaryotes is occupied by simple sequence repeats (SSRs). Although thesis sequences have sparked great interest as a means of studying genetic variation, linkage mapping and evolution, little attention had been paid to the chromosomal distribution and cytogenetic diversity of these sequences. This paper report the long-range organization of all possible classes of mono-, di- and tri-nucleotide SSRs in Brassica rapa. Fluorescence in situ hybridization (FISH) was used to characterize the cytogenetic diversity of SSRs among morphotypes of B. rapa ssp. chinensis. The proportion of different SSR motifs varied among morphtypes of B. rapa, with trinucleotide SSRs more prevalent in the genome of B. rapa ssp. chinensis. The chromosomal characterizations of mono-, di- and tri-nucleotide repeats have been acquired. The data has revealed the non-random and motif-dependent chromosome distribution of SSRs in different morphtypes, and allowed the relative variability characterized by SSRs amount and similar chromosomal distribution in centromeric/peri-centromeric heterochromatin. The differences of SSRs in the abundance and distribution indicated the driving force of SSRs in relationship with the evolution of B. rapa species. The results provided a comprehensive view on the SSR sequence distribution and evolution for comparison among morphtypes B. rapa ssp. chinensis.